Some properties of K-Operator Frame in Hilbert $C^{*}$-modules (Jurnal Matematika, Statistika dan Komputasi, 2022)
In this paper, we present some properties of K-operator Frame in Hilbert $C^{*}$-modules.Topics that will be discussed include: K-operator Frame and Dual K-operator frame in Hilbert $C^{*}$-modules.We will also study K-operator Frame in two Hilbert $C^{*}$-modules with different $C^{*}$-algebras.
Keywords: $K$-Operator Frame; Dual $K$-operator frame; $C^{*}$-algebra; Hilbert $C^{*}$-modules; Tensor Product